(untitled) (Journal of Shaheed Suhrawardy Medical College, 2013)
Background: Circumcision is the most common surgical procedure performed in boys through out the world. Meatal stenosis is one of its late complications. Objective: The aim of the present study is to see the effectiveness of use of lubricants vaseline-petrelium jelly) during arumcision meatal stenosis. Methodology: A randomized control trial was performed, in which two groups of boys younger than two years old underwent circumcision according to dissection (sleeve) method. The parents in the study groups were strictly instructed to use petroleum jelly on the meatus and circumcision site at every morning or after each diaper change where necessary for three months. On the other hand parents in the control group were instructed not to use any lubricants or topical medication on the same site. The boys were followed up regularly and evaluated for meatal stenosis, bleeding and infection. Results: A total of 120 boys were recruited & in each group comprised of 60 boys. None of the boys in the study group develop meatal stenosis , but 6(10%) in the control group develop meatal stenosis (p< 0.05 ). Infection of the circumcision site was seen in 1 (0.6%) and 3 (5%) children in the lubricant and control groups, respectively (p<0.05) and bleeding was seen in 3 (5.0%) and 6(10.0%) respectively. Conclusion: Based on the findings of this study, it seems logical to use a lubricant jelly for prevention of post circumcision meatal stenosis and other complications. DOI: http://dx.doi.org/10.3329/jssmc.v5i1.16204 J Shaheed Suhrawardy Med Coll, 2013;5(1):35-38